Optimizing the Role of Bhabinkamtibmas Through Community Policing to Improve Kamtibmas Stability In the Jurisdiction Of The Salatiga Police - Grizzly Joe Litaay (Police Studies Review, 2022)
Bhabinkamtibmas has the main task to maintain community development, early detection and mediation / negotiation in order to create conducive conditions in the village / village. One of the activities carried out by Bhabinkamtibmas is the Polmas activity which aims to invite the community through the Polri partnership so that it can detect kamtibmas problems in the environment. and find a solution to the problem. In the jurisdiction of the Salatiga Police , the condition of kamtibmasnya is still not conducive. There are still many cases of criminal acts that occur this shows the unstable condition of security and public order in the jurisdiction of the Salatiga Police. For this reason, it is necessary to optimize the role of Bhabinkamtibmas through community policing to improve the stability of kamtibmas in the salatiga police law wizard. In discussing this research, researchers used SWOT theory, Management theory, Bhabinkamtibmas Concept, Polmas Concept, and Kamtibmas Concept in discussing the findings of problems in this study. This research uses a qualitative approach. The focus of this research is on optimizing the role of Bhabinkamtibmas through community policing to improve the stability of kamtibmas in the jurisdiction of the Salatiga Police. In this study the data source used is interviews with Bhabinkamtibmas members as well as the public. Data validity uses data triangulation. Data analysis techniques used in the form of data reduction, data presentation, and inference. The result of the research conducted by researchers is that there are still obstacles in the implementation of Polmas by Bhabinkamtibmas Salatiga Police. Obstacles include lack of material, lack of supervision, and lack of careful planning. In addition, there are still obstacles in the community that still cannot get closer to the environment. Based on the results of this study, problem solving that can be done, among others , binluh planning by polmas must be filled carefully and to continue to be checked again. In addition, the need to build communication that can be through whatsapp group social media to speed up the handling of cases that occur so that the stability of kamtibmas can be maintained.